Characteristics and adaptation of skeletal muscle to endurance exercise - Kohn, T. A. (2005)
Skeletal muscle adapts to stimuli by modifying structural and metabolic protein expression. Furthermore, a muscle group may vary within itself to accommodate specialisation in regions. Structural and metabolic characteristics of an individual are regulated partly by genotype, but contraction duration and intensity may play a greater role in muscle phenotype. The aims of this dissertation were to investigate: structural and metabolic regionalisation in a muscle group, possible relationships between training volume and intensity and hybrid fibres, muscle characteristics of athletes from two different ethnic groups, and muscle adaptation in already well-trained athletes subjected to high intensity interval training. Myosin heavy chain (MHC) isoform content and citrate synthase (CS) activities were measured in the Quadriceps femoris (QF) muscle of 18 female rats. Muscle was divided into superficial, middle and deep, distal, central and proximal parts. MHC IIb and IIx were more abundant in superficial regions (P < 0.05) with low CS activities compared to deeper parts. Isoform content varied along the length of deep regions. This study showed that the QF has regional specialisation. Therefore, standardisation of sampling site is important. Hybrid fibre proportions in muscle biopsies of 12 middle distance runners and 12 non-runners were investigated. MHC IIa/IIx correlated with training volume/week in runners (r = -0.66, P < 0.05) and MHC IIa/IIx correlated with exercise hours/week in non-runners (r = -0.72, P < 0.01). Average preferred racing distance (PRDA) correlated better with MHC IIa/IIx in runners (r = -0.85, P < 0.001). MHC IIa/IIx may therefore be more closely related to exercise intensity than previously thought. Fibre type characteristics and performance markers were investigated in 13 Xhosa and 13 Caucasian distance runners, matched for performance, training volume and PRDA. Xhosa runners had less MHC I and more MHC IIa fibres in muscle biopsies than Caucasian runners (P < 0.05). Xhosa runners had lower plasma lactate at 80% peak treadmill speed (PTS) (P < 0.05), but higher lactate dehydrogenase (LDH) (P < 0.01) and phosphofructokinase (P = 0.07) activities in homogenate muscle samples. LDH activities in MHC I (P = 0.05) and IIa (P < 0.05) fibre pools were higher in Xhosa runners. Xhosa athletes may thus have a genetic advantage or they may have adapted to running at a higher intensity. Six weeks of individually standardised high intensity interval treadmill training (HIIT) were investigated in 15 well-trained runners. PTS increased after HIIT (P < 0.01), while maximum oxygen consumption (VO2max) only showed a tendency to have increased as a result of HIIT (P = 0.06). Sub-maximal tests showed lower plasma lactate at 64% PTS (P = 0.06), with lower heart rates at workloads from 64% to 80% PTS (P < 0.01) after HIIT. No changes were observed for cross-sectional area, capillary supply and enzyme activities in homogenates muscle samples. LDH activity showed a trend (P = 0.06) to have increased in MHC IIa pools after HIIT. Higher HIIT speed was related to decreases in MHC I fibres, but increases in MHC IIa/IIx fibres (r = -0.70 and r = 0.68, respectively, P < 0.05). Therefore, HIIT may alter muscle fibre composition in well-trained runners, with a concomitant improvement in performance markers.